Methods for production of uniform small-sized polymersome with rigid membrane. Issue 24 (12th May 2016) - Men, Yongjun; Peng, Fei; Tu, Yingfeng; van Hest, Jan C. M.; Wilson, Daniela A.
Abstract : We report a facile methodology for the formation of uniform small-sized poly(ethylene glycol)- block -polystyrene (PEG- b -PS) polymersomes, via extrusion and sonication methods by using organic solvent as plasticizing agent. Abstract : We report a facile methodology for the formation of uniform small-sized poly(ethylene glycol)- block -polystyrene (PEG- b -PS) polymersomes, via extrusion and sonication methods by using organic solvent as plasticizing agent. The obtained polymersomes have diameters less than 100 nm. The size and size distribution depend on the organic solvent content and sonication time. The small-sized polymersomes are able to carry both hydrophobic and hydrophilic dyes.